THE IMMUNITY RESISTANCE OF WORM-BLOOD ANIMALS, MAKING THE SUB TOXIC DOSES OF ORGANIC MIXES - Sirenko, E.V.; Zhykov, V.I.; Kycherenko, E.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
The ability of sub toxic doses of organic mixes to damage prolipheration and differentiation immune-cells, to disorders functional activity cell and humeral immunity was shown.  This rezalts presented the negative status of hole resistans of organism/ It was revealed the occurring of hole-cell, the occurring of functional activity splenar – cells, timus and the decrease of plasma – cells reaction in the splenar and lymphatic nodules, demeging the adaptivity of organism.